ANALYTICAL QBD INTEGRATED RP-HPLC METHOD DEVELOPMENT AND OPTIMIZATION FOR HIGH-PRECISION QUANTIFICATION OF IBRUTINIB IN HYBRID NANOCARRIER SYSTEMS - BANGERA, PRAGATHI DEVANAND; KEERIKKADU, MAHESHA; TIPPAVAJHALA, VAMSHI KRISHNA; RATHNANAND, MAHALAXMI (International Journal of Applied Pharmaceutics, 2025)
Objective: This study optimizes, develops, and validates the reversed-phase high-performance liquid chromatography (RP-HPLC) assay to measure Ibrutinib (IBR) in bulk and nanoformulations. It is a highly sensitive and specific method. Methods: Chromatographic optimization was addressed using a methodical Design of Experiments (DoE) approach. Key method parameters (CMPs) were screened using the Taguchi Orthogonal Array (OA) design, and the outcomes were optimized using the Box-Behnken Design (BBD). Results: The optimal settings were the Acetonitrile (ACN) (50% v/v) as the mobile phase, a 1.043 ml/min flow rate, and a column oven temperature of 26 °C. Under these conditions, the following results were obtained: theoretical plates of 13,5050±19.9, a peak area of 171500.66±324.94 mV-min, a Retention time (Rt) of 8.12±0.011 min, and a Tailing factor (Tf) of 1.21±0.001. The procedure showed good linearity with detection and quantification limits of 4.74 ng/ml and 15.8 ng/ml, respectively, for the concentration range of 50-5000 ng/ml (R2=0.9997). Validation verified that the approach met regulatory requirements for precision, specificity, sensitivity, accuracy, and robustness. Moreover, the method showed selectivity towards IBR even in degradation products. Conclusion: The suggested RP-HPLC technique is good for regular pharmaceutical examination of IBR formulations. It has been effectively applied to identify and quantify IBR in hybrid nanocarriers and in in vitro drug release tests.